1949
DOI: 10.1021/ie50480a012
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Sulfur Compounds with Hydrogen Fluoride

Abstract: Extraction of individual organic sulfur compounds with anhydrous liquid hydrogen fluoride shows an orderly progression with changes in sulfur type, in molecular weight, or in configuration of substituent groups. Increased extraction is obtained in going from mercaptans to disulfides to thio ethers, but extraction is decreased with increasing molecular weight of a given type of sulfur compound. Whereas transition from primary to secondary to tertiary alkyl substituents results in progressively increased extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1952
1952
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The data indicate that within probable limits of analytical error, equilibrium may be attained with a contact time of 5 minutes or less. These results are in accordance with the theory previously proposed (11), that hydrogen fluoride extraction occurs as the result of an acid-base reaction. Further work has demonstrated that as little as 1 or 2 minutes is sufficient to achieve complete separation of phases, even with heavier stocks such as gas oil; this rapid separation is attributable to the extremely low viscosity and surface tension of hydrogen fluoride as well as to the large density differential between hydrogen fluoride and hydrocarbon.…”
Section: Effect Of Variables On Hydrogen Fluoride Extractionsupporting
confidence: 93%
See 1 more Smart Citation
“…The data indicate that within probable limits of analytical error, equilibrium may be attained with a contact time of 5 minutes or less. These results are in accordance with the theory previously proposed (11), that hydrogen fluoride extraction occurs as the result of an acid-base reaction. Further work has demonstrated that as little as 1 or 2 minutes is sufficient to achieve complete separation of phases, even with heavier stocks such as gas oil; this rapid separation is attributable to the extremely low viscosity and surface tension of hydrogen fluoride as well as to the large density differential between hydrogen fluoride and hydrocarbon.…”
Section: Effect Of Variables On Hydrogen Fluoride Extractionsupporting
confidence: 93%
“…A new development in this field-extraction with anhydrous hydrogen fluoride-offers interesting possibilities. The action of hydrogen fluoride toward individual sulfur compounds and the chemical aspects of hydrogen fluoride extraction have been described in a previous paper from this laboratory (11)', additional work on individual sulfur compounds has been reported by Barieau and Barusch (5) and by Meadow and White (12). Application of hydrogen fluoride extraction to refinery stocks has been discussed by Scafe (13), and by Schneider and coworkers (14, IB).…”
mentioning
confidence: 93%
“…Many other solvents, such as aniline, propylene, glycol, and furfural, have been proposed but are not completely satisfactory. Extraction of individual organic sulfur compounds with anhydrous hydrogen fluoride shows an orderly progression with changes in sulfur type, in molecular weight, or in configuration of substituent groups (154). This order is roughly the same as the order of adsorption observed for silica gel.…”
Section: Processes For Segregating Sulfur Compoundssupporting
confidence: 56%
“…Although they effect some desulfurization, the selectivities for sulfur compounds are too lo~v to make them attractive for desulfurization alone. Acidic solvents, such as hydrogen fluoride and sulfuric acid, show almost the opposite effect; they are highly selective for sulfur compounds but remove aromatics to only a slight extent (7)(8)(9). -4 solvent having intermediate properties would be useful where both desulfurization and aromatic removal are desired.…”
Section: He Increasing Sulfur and Aromatics Content Of Petroleummentioning
confidence: 99%
“…Extraction Studies. The effect of structure on complexing tendencies of sulfur compounds has been demonstrated by extraction from heptane solutions with anhydrous hydrofluoric acid (8,9). Similar studies with sulfur dioxide, both alone and promoted by aluminum chloride, were carried out to show the effect of promoter and to provide a comparison with hydrofluoric acid EFFECT OF PROMOTER.…”
Section: Studies With Individual Compoundsmentioning
confidence: 99%